The Ḥanafī Influence on the Approach of Baghdad Uṣūlī Scholars to Khabar al-Wāḥid - Peyman Ünügür Tekin (Turkish Journal of Shiite Studies)
The central argument of this study is the identification of a notable similarity between the khabar theories employed by Ḥanafīs and Baghdad Uṣūlīs. It is evident that Ḥanafīs established the theoretical framework of their khabar theory at a comparatively earlier point in time than Imāmīs. Accordingly, it can be posited that Ḥanafīs had a notable impact on Baghdad uṣūlī Scholars with regard to their khabar theory. In order to establish this similarity, the primary sources consulted are the uṣūl al-fiqh works of two schools.